2017
DOI: 10.15748/jasse.4.162
|View full text |Cite
|
Sign up to set email alerts
|

Numerical stability analysis of the local inertial equation with semi- and fully implicit friction term treatments: assessment of the maximum allowable time step

Abstract: Abstract. The local inertial equation (LIE) as a simple mathematical model has been widely used for flood simulation. So far, the maximum allowable time step of the discretized LIE with the conventional semi-implicit scheme has been believed to follow the standard Courant-Friedrichs-Lewy condition. However, we demonstrate that this is not true from the viewpoint of a numerical stability analysis considering the model non-linearity. In addition, a fully-implicit variant of the scheme with higher stability is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Stability analysis against a perturbed uniform flow is carried out to quantify stability conditions of the three schemes. The flow considered here is uni-directional, and the 1-D counterpart of the LIM (q = 0 and ∂h ∂ y = ∂z ∂ y = 0) is employed (Tanaka and Yoshioka, 2017). The initial condition is a uniform flow on a slope having a constant gradient.…”
Section: Consistency and Stability Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stability analysis against a perturbed uniform flow is carried out to quantify stability conditions of the three schemes. The flow considered here is uni-directional, and the 1-D counterpart of the LIM (q = 0 and ∂h ∂ y = ∂z ∂ y = 0) is employed (Tanaka and Yoshioka, 2017). The initial condition is a uniform flow on a slope having a constant gradient.…”
Section: Consistency and Stability Testsmentioning
confidence: 99%
“…It has been stated that the friction slope terms in 2and 3should be handled in a semi-implicit manner for numerical stability (Bates et al, 2010;de Almeida and Bates, 2013). However, recently, Tanaka and Yoshioka (2017) found that this discretization becomes unstable even when the classical Courant-Friedrichs-Lewy (CFL) condition is satisfied. An implicit scheme was developed as an alternative to the semi-implicit one (Tanaka and Yoshioka, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation